Perception of tourists and locals of the Esplanade as a performance arts centre. - Choo, Trini Shi Li. (2008)
A survey on how tourists and locals perceive the Esplanade - Theatres on the Bay to be as an arts centre and general factors that affect their decision to watch an arts performance.